Perception of non-muslims towards islamic banking products and services/ Nur Adibah Ab Aziry - Ab Aziry, Nur Adibah (2019)
Islamic banking products and services are gaining familiar and popular among public either Muslims or non-Muslims nowadays. However, there are still a huge gap between Islamic banks and Commercial banks. Hence, this research study aims to analyze the perception of non-Muslims towards Islamic banking products and services among Petronas staff at KLCC. The purpose of this study also to investigate the awareness and understanding among them. At the same time, this study also tries to determine the relationship between their awareness and understanding with their perception. The analysis of this research involved 46 respondents, all of them are from Petronas staff at KLCC, Malaysia. For the methods of analysis, Pearson Correlation Coefficient and Simple Linear Regression (SLR) was adopted to analyze the results. The results show that all the respondents have a lack of awareness and understanding towards Islamic banking products and services that provided. The understanding level of non-Muslims towards Islamic banking concept are at average level and they are totally do not know on Arabic terms that used by Islamic banking. For the perception of non-Muslims towards Islamic banking products and services are varied and more tend to negative or moderate perception. In addition, non-Muslims are preferring to use Conventional banking system rather than Islamic banking system and lack of acceptance towards it among them. Lastly, this study also provides recommendation for Islamic banking institutions to attract non-Muslims and also for future research regarding Islamic banking.